ISLAMIC BANK SUSTAINABILITY IN INDONESIA; VALUE AND FINANCIAL PERFORMANCES BASED ON SOCIAL RESPONSIBILITY AND GREEN FINANCE - Helma Malini (Cepalo, 2021)
This paper investigates the sustainability perspective of Islamic banks' financial decisions, performance, and corporate value where Corporate Social Responsibility (CSR) and green finance are moderation variables. The analysis method used multivariate statistical methods, structural equation modelling with the WarpPLS software program and testing panel data regression models using the E-Views software program. The datasets used involves 34 Islamic banks in Indonesia. This study found a significant relationship between CSR and green finance implementation to financial decisions, financial performance, and corporate value of Islamic banks in Indonesia. However, the relationship is heterogeneous or dissimilar across different quantiles. This means that CSR and green finance implementation only achieve short-term profit, not long-term sustainability. The study also reveals that corporate social responsibility contributes the most to Islamic banks' investment decisions and market value. Thus, policies focusing on integrated CSR in Islamic banking are required to improve sustainability opportunities.